Holistic narratives of the renovation experience: Using Q-methodology to improve understanding of domestic energy retrofits in the United Kingdom. (August 2018) - Kerr, Niall; Gouldson, Andy; Barrett, John
Abstract: The energy efficient retrofit of existing building stocks can help to address various social, economic and environmental objectives. As the most cost-effective and least disruptive retrofit options have regularly been implemented as a priority, initiatives that seek to encourage continued retrofit are likely to require thoughtful improvements in their design. Understanding the population of households that may be interested in retrofit as a heterogeneous rather than a homogenous group is a critical part of improving support for retrofit. In this research, we use Q-methodology to disaggregate the home owner-occupier population of the UK and create narratives that represent their experience of home renovations. We consider the experience of general home renovations as typically households do not see these as distinctive from energy efficient retrofit. The narratives present a holistic perspective by incorporating a comprehensive range of the influences on the renovation experience. The developed narratives – 'Organised and seeking greater comfort', 'Settled and performing a functional upgrade', 'Growing and needing a family home' and 'A lot to do and no time like the present' – provide the opportunity to better understand those making renovation decisions and subsequently develop more appropriate interventions to promote retrofit.